Instability of thin steel cylindrical shells under bending. (April 2019) - Kumar Yadav, Kshitij; Gerasimidis, Simos
Abstract: Bending of steel cylindrical shells is generally characterized by the interaction among ovalization, bifurcation, and material plasticity when the slenderness of the shell is relatively low. It is a nonlinear phenomenon, which is dictated by buckling-sensitivity of the shells to imperfections. The behavior of cylindrical shells under bending and its imperfection sensitivity have not been yet fully understood for all the range of dimensions. This study investigates the buckling behavior and imperfection sensitivity of thin steel cylindrical shells under pure bending, focusing on a specific range of slendernesses, which are commonly found in energy structures such as tall wind turbine towers ( 60 < R / t < 120 ) . The inelastic localized buckling instability is studied using computational methods to assess the critical load of the thin steel cylindrical shells. One of the main goals is to predictively describe the buckling sensitivity of the shells and to the provide relationships between the knockdown factor and geometric imperfections. In addition, an extensive study has been done to investigate the impact of steel strain-hardening models on the bending behavior. Four types of plasticity models are utilized to observe the effect of strain-hardening models on the bending behavior and imperfection sensitivity of the thin steel cylindrical shells: a bilinear and three versions of the Ramberg-Osgood plasticity model. Abstract : Highlights: Buckling and imperfection sensitivity of thin cylindrical shells under pure bending. The influence of material-hardening models when the R/t varies from 60 to 120. Thin cylinders (60 < R/t <120) are highly imperfection sensitive under bending. Strain-hardening models play a very impactful role on the bending behavior.